Zoektocht en keuzes - Mbarki, Sofyan (Religie & Samenleving, 2015)
Based on my personal history as a young man of Maroccan origin, born in the Netherlands, and as a teacher and a member of the municipal council of Amsterdam, I reflect upon the choices I made in life. What made me resilient against radical forms of Islam and how can we prevent others to make radical choices? Parents have a role here, showing to be interested in the search for meaning of their children and also being well aware of their whereabouts and the friends they associate with. Furthermore profound religious education as critical counterbalance against radical ideologies is necessary. And, of no less importance, is a welcoming attitude to Muslims, to make them feel part of the Dutch society.